Controlling H*- and J-aggregation of an indotricarbocyanine dye in aqueous solutions of inorganic salts - Belko, Nikita V.; Samtsov, Michael P.; Lugovski, Anatoly P. (Journal of the Belarusian State University. Physics, 2020)
Aggregation process of a symmetrical cationic indotricarbocyanine dye in aqueous medium was studied. It was shown that self-assembled H*-aggregates with an absorption peak at 514 nm as well as J-aggregates with an absorption peak at 777 nm can be obtained. Both of the aggregate types are non-fluorescent. High concentration of a desired aggregate type can be obtained and stabilized by changing ionic strength and pH of the solution. At ionic strength of 170 mmol/L and pH 7.4 J-aggregates are stable. Decreasing pH as well as ionic strength leads to demise of J-aggregates and concomitant formation of H*-aggregates. Increasing temperature leads to a faster H*-aggregate formation. The type of aggregates can be changed by heating and subsequent cooling of the solution. An organic compound forming both H*- and J-aggregates has never been observed before. The fact that the H*- and J-bands are narrow, the shift between them is significant, the J-band is located in the far-red spectral region, and the type of aggregates can be controlled makes these objects promising for future applications.